2021
DOI: 10.1101/2021.07.22.453400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How clustered protocadherin binding specificity is tuned for neuronal self/non-self-recognition

Abstract: The stochastic expression of fewer than 60 clustered protocadherin (cPcdh) isoforms provides diverse identities to individual vertebrate neurons and a molecular basis for self/non-self-discrimination. cPcdhs form chains mediated by alternating cis and trans interactions between apposed membranes, which has been suggested to signal self-recognition. Such a mechanism requires that cPcdh cis dimers form promiscuously to generate diverse recognition units, and that trans interactions have precise specificity so th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…martensii ( 34 ), in which the constant region affects the formation and size of cell aggregates. Biophysical experiments showed that cis interactions of cPcdh are generally promiscuous but with a preference for the formation of heterologous cis dimers ( 59 ). If this finding holds true in the sDscam family, we would expect that differences in the constant region would affect cis interactions.…”
Section: Discussionmentioning
confidence: 99%
“…martensii ( 34 ), in which the constant region affects the formation and size of cell aggregates. Biophysical experiments showed that cis interactions of cPcdh are generally promiscuous but with a preference for the formation of heterologous cis dimers ( 59 ). If this finding holds true in the sDscam family, we would expect that differences in the constant region would affect cis interactions.…”
Section: Discussionmentioning
confidence: 99%